Instagram and political storytelling among Malaysian politicians during the 14th General Election - Mohamed, Shafizan (2018)
This paper delineates the strategic use of Instagram in the Malaysian 14th General Election held in May 2018. Based on a comprehensive visual analysis of Instagram posts from several prominent candidates, this contribution analyzes important areas of digital storytelling on Instagram. By identifying relevant image types central to the self-representation of the candidates, this study shows how Malaysian politicians makes use of a digital platform in order to project and manage desired images.